Казахские термины родства в русскоязычных СМИ Казахстана - Смирнов, Иван (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The article presents Kazakh kinship terms that are actively used in the Russian-language media of Kazakhstan. An extensive network of family relationships maintains a hierarchy between relatives and influences the social status of each participant. In the Russian-language media space, a small part of Kazakh words related to family ties is represented. It is worth noting that the examples given in the article are in most cases used in Internet sources and are less common in the official press. The process of morphological transformation concerns every lexeme of kinship in the Kazakh that is actively used in the Russian.
Kazakh terms of kinship system in the Russian-language media of Kazakhstan
В статье представлены казахские термины родства, которые используются в русскоязычных средствах массовой информации в Казахстане.
Keywords: Kazakh; kinship system; Russian; kinship terminology; media